Strong-ties and weak-ties rationalities: toward a mental model of the consequences of kinship intensity - Yeh, Kuang-Hui; Terpstra Tong, Jane; Ting, Rachel Sing-Kiat; Bond, Michael Harris; Khosla, Meetu; Yadav, Virendra Pratap; Shukla, Shashwat; Liu, Charles; Sundararajan, Louise (Frontiers in Psychology, 2024)
There is growing evidence of the connection between variations in kinship intensity and cross-cultural differences in psychological traits. Contributing to this literature on kinship intensity, we put forward a mental model to explain the enduring connection between ancestral niche and psychological traits. Our model posits that two primary orientations or dispositions – strong-ties and weak-ties rationalities – have co-evolved with our ancestral niches to perpetuate-- by internalizing and reproducing-- the social structure (such as preferences for certain attitudes, values, and beliefs) of the ancestral niche. The findings from 1,291 participants across four societies - China, India, Taiwan, and the United States - support our hypothesis that strong-ties (weak-ties) rationalities, when activated, will endorse strong-tie (weak-ties) values and beliefs. This proposed model contributes to the toolbox of cultural and cross-cultural psychology in a twofold sense: First, in addition to the index of kinship intensity, it offers a measure of kin-based rationality as another predictor of psychological traits; second, it renders intelligible the niche and rationality disconnect prevalent in the globalizing era.